2008
DOI: 10.1002/hyp.7063
|View full text |Cite
|
Sign up to set email alerts
|

Monotonic trend and abrupt changes for major climate variables in the headwater catchment of the Yellow River basin

Abstract: Abstract:On the basis of the mean air temperature, precipitation, sunshine duration and pan evaporation at 23 meteorological stations in the headwater catchment of the Yellow River basin from 1960 to 2001, the long-term monotonic trend and abrupt changes for major climate variables have been investigated. The plausible monotonic trend of annual climatic time series are detected using a non-parametric method. The abrupt changes have been investigated in terms of a 5 year moving averaged annual series, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…In China, Wang et al [17] found an abrupt decrease in the flood-season precipitation around the year of 1979 based on weather stations in the Haihe River Basin. Zhao et al [18] confirmed an abrupt decrease in precipitation during the late 1970s and middle 1980s was also observed in the upper Yellow River Basin.…”
Section: Introductionmentioning
confidence: 74%
“…In China, Wang et al [17] found an abrupt decrease in the flood-season precipitation around the year of 1979 based on weather stations in the Haihe River Basin. Zhao et al [18] confirmed an abrupt decrease in precipitation during the late 1970s and middle 1980s was also observed in the upper Yellow River Basin.…”
Section: Introductionmentioning
confidence: 74%
“…Some authors have also attempted to detect the trend and abrupt changes in time series separately (e.g. Zhao et al 2008), but this approach is not statistically satisfactory because the conclusions obtained from different tests may not be compatible (Shao et al 2010). Though a single trend test is considered appropriate for trend testing and detection with specified start and end times, it does not show whether any changes are due to gradual or abrupt occurrences .…”
Section: Introductionmentioning
confidence: 99%
“…But summer precipitation (from June to September) showed a tendency to decline. Zhao et al (2007) reported that over the past 40 years the annual mean temperature has significantly increased by 0.8…”
Section: Introductionmentioning
confidence: 99%